Wood vinegar obtained by multi-stage catalytic hydrothermal method and its preparation and antibacterial application
Through the use of multi-stage catalytic hydrothermal method and NiO/CaO·B2O3 composite catalyst, the problem of low organic components in the preparation of wood vinegar liquid by hydrothermal method is solved, significantly improving the antibacterial properties and organic components content, and the recycling and utilization of the catalyst is realized.
Patent Information
- Application Number
- CN202211220148.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-10-08
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2042-10-08
AI Technical Summary
The existing hydrothermal method prepares low organic components in wood vinegar liquid, resulting in reduced antibacterial performance and is not conducive to storage and transportation.
The multi-stage catalytic hydrothermal method is used to catalyze the hydrothermal pyrolysis of biomass using the NiO/CaO·B2O3 composite catalyst, and the content of organic components in the wood vinegar liquid is significantly increased through multi-stage hydrothermal reaction, especially antibacterial components such as phenols and acids.
It significantly improves the antibacterial properties of wood vinegar liquid, increases the content of organic components, improves its storage and transportation conditions, and realizes the recycling and utilization of catalysts.
Smart Images

Figure BDA0003877459260000261 
Figure BDA0003877459260000271 
Figure HDA0003877459270000011
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of wood vinegar, and particularly relates to wood vinegar obtained by a multi-stage catalytic hydrothermal method and its preparation and antibacterial application. Background Art
[0002] Biomass is one of the most abundant sources of renewable resources, but its current utilization rate is very low. For a long time, the utilization of lignocellulosic biomass has been mainly based on direct combustion. In recent years, as people pay more and more attention to environmental changes and the rational use of resources, the liquefaction of lignocellulose to produce high-value chemicals has attracted more and more attention from researchers. Wood vinegar is a reddish-brown weakly acidic liquid mixture, mainly composed of water and organic matter. The organic matter contains rich organic acids (formic acid, acetic acid, propionic acid, valeric acid, etc., accounting for 10-30% of the total organic content) and phenols (phenol, guaiacol, 2,6-dimethoxyphenol, hydroquinone, etc., accounting for 25-45% of the total organic content), which gives wood vinegar excellent antibacterial properties and has great application value in agriculture, forestry, animal husbandry, medicine and other industries. Existing studies have shown that the antibacterial properties of wood vinegar are proportional to the content of organic acids and phenols contained therein. Among them, phenols are the main factor affecting the antibacterial properties of wood vinegar.
[0003] Wood vinegar is mainly derived from the high-temperature pyrolysis products of lignocellulosic biomass. The preparation of wood vinegar mainly adopts the traditional dry distillation pyrolysis method, that is, crude biomass such as wood, agricultural and forestry waste, etc. are pyrolyzed at 300-550°C under anaerobic or anoxic conditions, and the pyrolysis gas is condensed to obtain crude wood vinegar. For example, Wu et al. (Bioresource Technology, 2015, 179: 98-103) and Hou et al. (Journal of Fuel Chemistry, 2015, 43 (12): 1439-1445) used fir and cotton stalks as raw materials to prepare wood vinegar using traditional pyrolysis methods, with a yield of 40-45 ml / 100 g crude biomass, and the tar content in wood vinegar is relatively high, reaching 20%. Therefore, the traditional pyrolysis method for preparing wood vinegar has the disadvantages of low yield, high temperature causing biomass decomposition to produce tar, and high content of harmful substances, which limits the large-scale production and high-value utilization of wood vinegar.
[0004] Compared with the traditional dry distillation pyrolysis method, the hydrothermal method for preparing wood vinegar has the characteristics of relatively mild conditions (pressure of 1.5-25Mpa, temperature of 200-350°C), simple process and high yield (water acts as a solvent and participates in the pyrolysis process of biomass), low cost and easy regulation, and because the biomass is hydrothermally decomposed at a relatively low temperature, the tar content in the prepared wood vinegar is low, which has attracted people's attention in recent years. Chinese patent application CN106590717 discloses a method for preparing wood vinegar by biomass hydrothermal method, which mixes biomass such as cotton stalks, fir sawdust, bamboo sawdust and water in a ratio of 1:3-1:16 at 200-350°C, 1.5-16.6Mpa and a reaction time of 5-90min to prepare hydrothermal wood vinegar. However, compared with the traditional dry distillation pyrolysis method, the content of organic components in hydrothermal wood vinegar is low, resulting in reduced antibacterial properties and is not conducive to its storage and transportation. Chinese patent application CN106753501 prepares wood vinegar with a small amount of oxidant in the hydrothermal process, and its yield reaches 80-90%, and the output reaches 80-100 ml / 10 g biomass. Wang et al. (Bioresource Technology, 2018, 263: 289-296) further studied the effect of oxidant H2O2 on wood vinegar components in the hydrothermal process, and found that the addition of oxidant increased the yield of wood vinegar, reduced the optimal pyrolysis temperature and time of biomass, and significantly increased the acid content in wood vinegar. However, H2O2 significantly increases the reaction pressure at hydrothermal temperature, promotes the demethylation and demethoxylation of organic matter, reduces the content of methoxyphenols in wood vinegar, and reduces its antibacterial properties. Therefore, how to increase the content of organic components in the preparation of wood vinegar by hydrothermal method, especially the selective increase of the content of certain specific effective components with antibacterial properties such as methoxyphenols, organic acids, phenols, etc., is an effective way to improve the quality of wood vinegar by hydrothermal method and promote the widespread application of wood vinegar.
[0005] There have been a lot of studies on the application of catalysts in biomass hydrothermal pyrolysis. Studies have shown that catalysts can not only promote the degradation of biomass and reduce the yield of solid residues after hydrothermal pyrolysis, but also moderately reduce the hydrothermal reaction conditions, including reaction temperature, pressure and reaction time. Selecting a suitable catalyst can also selectively increase the content of certain specific effective components in wood vinegar, thereby improving the antibacterial properties of wood vinegar. At present, the catalysts used in the field of biomass hydrothermal pyrolysis and hydrothermal liquefaction can be divided into homogeneous catalysts such as (acids, bases, basic salts, etc. soluble in solvents) and heterogeneous catalysts (metal catalysts or supported catalysts, etc.). For homogeneous catalysts, H2SO4, KOH, K2CO3, etc. are currently mainly used. Although they can promote the hydrothermal decomposition of biomass under certain conditions, they are dissolved in the product and will change the acidity and alkalinity of the liquid phase in the hydrothermal product to a certain extent, which limits their use in the preparation of wood vinegar and are generally less used.
[0006] Heterogeneous catalysts are easy to separate and remove, and are expected to be used in the preparation of hydrothermal wood vinegar. At present, heterogeneous catalysts used for hydrothermal pyrolysis of biomass mainly include metal catalysts such as Fe powder, Zn powder, Ni powder, etc. and metal oxides such as Al2O3, CuO, etc.; non-metallic catalysts such as calcium borate, carbon, etc. and supported catalysts such as zeolite molecular sieves. Kubilay Tekin et al. (The Journal of Supercritical Fluids, 2012, 72, 134-139) used calcium borate stone powder as a catalyst for hydrothermal liquefaction of beech, significantly increasing the yield of bio-oil and reducing the content of furfurals, but the content of organic matter in the water phase is still low, and its antibacterial property is difficult to improve. In addition, the calcium borate stone powder after the reaction is mixed with the hydrothermal residue, which is difficult to separate and recover. The unmodified calcium borate stone powder cannot be directly used as a catalyst to prepare hydrothermal wood vinegar with high yield and excellent antibacterial property. Therefore, the preparation of a low-cost heterogeneous catalyst with oxidation properties and easy separation and recovery is the key to preparing high-yield wood vinegar with efficient antibacterial properties. Summary of the invention
[0007] In order to solve the shortcomings and deficiencies of the prior art, the primary purpose of the present invention is to provide a method for preparing wood vinegar by multi-stage catalytic hydrothermal method.
[0008] The method of the present invention is a multi-stage catalytic hydrothermal method for preparing wood vinegar. First, a NiO / CaO·B2O3 composite catalyst is prepared by a coprecipitation method, and then the NiO / CaO·B2O3 composite catalyst is used to catalyze the hydrothermal pyrolysis of biomass to obtain wood vinegar. Compared with the existing simple hydrothermal technology for preparing wood vinegar, the addition of the NiO / CaO·B2O3 composite catalyst during the hydrothermal process is beneficial to catalyze the conversion of furfural produced by the decomposition of biomass into antibacterial components such as organic acids and phenols, while increasing the content and yield of organic components in the aqueous phase, further enhancing the antibacterial properties of wood vinegar. The method of the present invention utilizes the magnetic properties of NiO in the composite catalyst to recover the catalyst from the hydrothermal residue to achieve the purpose of reuse. In order to further increase the content of organic components in wood vinegar, after the first-stage hydrothermal treatment, the mixture in the reactor is separated to obtain the first-stage hydrothermal wood vinegar, a certain amount of biomass powder and NiO / CaO·B2O3 composite catalyst are added to the first-stage hydrothermal wood vinegar, and the second-stage hydrothermal treatment is performed to obtain the second-stage hydrothermal wood vinegar, and at least three-stage hydrothermal reactions are performed by analogy. Finally, the wood vinegar obtained by multi-stage hydrothermal treatment is kept at low temperature and away from light for a certain period of time, and then the middle layer is extracted to obtain refined hydrothermal wood vinegar. After multi-stage hydrothermal treatment, the content of organic matter in the wood vinegar is significantly increased, which effectively solves the problem of low content of organic components in the wood vinegar prepared by the hydrothermal method.
[0009] Another object of the present invention is to provide a hydrothermal wood vinegar prepared by the above method. The crude wood vinegar prepared in the present invention is a light yellow clear transparent liquid, and the hydrothermal wood vinegar obtained after refining is a light brown clear transparent liquid with a density of 1.01 to 1.04 g / cm 3 , pH value is 3.5-4.5, the content of total organic matter reaches 4.80-5.20 g / L (calculated as total organic carbon content), and the total amount of effective components such as organic acids and phenols accounts for 50-70% of the total organic matter.
[0010] Another object of the present invention is to provide the application of the wood vinegar prepared by the hydrothermal method in the antibacterial field.
[0011] The purpose of the present invention is achieved through the following technical solutions:
[0012] A method for preparing wood vinegar by multi-stage catalytic hydrothermal method comprises the following steps:
[0013] (1) dispersing calcium borate in a nickel nitrate hexahydrate solution at a molar ratio of calcium to nickel of 1 to 4:11, allowing to stand after being evenly dispersed, drying, and calcining to obtain a nickel oxide / calcium borate composite catalyst;
[0014] (2) using water as a reaction medium, hydrothermally reacting the biomass with the nickel oxide / calcium borate composite catalyst at 200-350° C. for 0.5-2 h, filtering to obtain a first-grade hydrothermal wood vinegar solution, and recovering the nickel oxide / calcium borate composite catalyst;
[0015] (3) adding the biomass and the nickel oxide / calcium borate composite catalyst to the primary hydrothermal wood vinegar solution, hydrothermally reacting at 200-350° C. for 0.5-2 h, filtering to obtain the secondary hydrothermal wood vinegar solution, and recovering the nickel oxide / calcium borate composite catalyst;
[0016] (4) Referring to step (3), the biomass and the nickel oxide / calcium borate composite catalyst are added to the N-grade hydrothermal wood vinegar solution, and the reaction is carried out at 200-350° C. for 0.5-2 h, and filtered to obtain the N+1-grade hydrothermal wood vinegar solution, and the nickel oxide / calcium borate composite catalyst is recovered at the same time;
[0017] N is an integer and ≥ 2, that is, the operation of repeatedly adding biomass and nickel oxide / calcium borate composite catalyst to the latest hydrothermal wood vinegar to carry out hydrothermal reaction is performed to obtain multi-stage catalytic hydrothermal crude wood vinegar, and after layering, the middle aqueous phase is taken to obtain refined hydrothermal wood vinegar.
[0018] Preferably, the calcium borate in step (1) is CaO·B2O3·2H2O; the weight ratio of CaO·B2O3·2H2O to Ni(NO3)2·6H2O is 0.5 to 2:10.
[0019] Preferably, the mass concentration of the nickel nitrate hexahydrate solution in step (1) is 5-15%.
[0020] Preferably, the standing time in step (1) is 1 to 5 hours.
[0021] Preferably, the drying temperature in step (1) is 60-100° C. and the drying time is 5-15 hours.
[0022] Preferably, the calcination temperature in step (1) is 300-400° C. and the time is 2-4 hours; the calcination is carried out in a nitrogen and / or inert gas atmosphere, wherein the inert gas refers to a rare gas.
[0023] Preferably, the mixture obtained after calcination in step (1) is ground, washed with water, filtered, and dried to obtain the nickel oxide / calcium borate composite catalyst.
[0024] Preferably, the biomass in steps (2) to (4) is biomass powder, that is, the biomass is crushed before the reaction so that its particle size is ≤0.2 mm to obtain biomass powder.
[0025] Preferably, the biomass in steps (2) to (4) is agricultural and forestry waste, specifically at least one of corn stalks, bagasse, corn cobs, cotton stalks and wood fibers, and the wood fibers are at least one of poplar, bamboo and masson pine.
[0026] Preferably, the weight ratio of the biomass to the nickel oxide / calcium borate composite catalyst in steps (2) to (4) is 10:1 to 3.
[0027] Preferably, the amount of biomass used in steps (2) to (4) is the same, and the amount of nickel oxide / calcium borate composite catalyst used is the same.
[0028] Preferably, the hydrothermal reactions in steps (2) to (4) are carried out in a high-pressure reactor (when heated to a corresponding temperature in a closed space, huge steam pressure will be generated, forming a high-pressure environment, and no additional pressure needs to be applied).
[0029] Preferably, the temperature of the hydrothermal reaction in steps (2) to (4) is 230 to 270° C. and the time is 1 to 2 h; or the temperature is 270 to 300° C. and the time is 0.5 to 1 h.
[0030] Preferably, the weight ratio of the biomass to water in step (2) is 1:10-20; more preferably 1:10-12.
[0031] Preferably, in the reaction system of steps (3) to (4), the weight ratio of biomass to liquid is 1:10 to 20. When the initial hydrothermal wood vinegar solution cannot meet the weight ratio of biomass to liquid of 1:10 to 20, water is added to supplement the reaction.
[0032] Preferably, in step (4), N satisfies 2≤N≤5.
[0033] Preferably, the multi-stage catalytic hydrothermal crude wood vinegar obtained in step (4) is allowed to stand at low temperature and away from light for 10 to 30 days to achieve stratification, more preferably for 15 to 20 days.
[0034] The above-mentioned multi-stage catalytic hydrothermal method for preparing wood vinegar comprises the following steps:
[0035] (1) dispersing calcium borate into a nickel salt solution in a molar ratio of calcium to nickel of 1 to 4:11, allowing to stand after being evenly dispersed, drying, and calcining to obtain a nickel oxide / calcium borate composite catalyst;
[0036] (2) using water as a reaction medium, hydrothermally reacting the biomass with the nickel oxide / calcium borate composite catalyst at 200-350° C. for 0.5-2 h, filtering to obtain a first-grade hydrothermal wood vinegar solution, and recovering the nickel oxide / calcium borate composite catalyst;
[0037] (3) adding the biomass and the nickel oxide / calcium borate composite catalyst to the primary hydrothermal wood vinegar solution, hydrothermally reacting at 200-350° C. for 0.5-2 h, filtering to obtain the secondary hydrothermal wood vinegar solution, and recovering the nickel oxide / calcium borate composite catalyst;
[0038] (4) adding the biomass and the nickel oxide / calcium borate composite catalyst to the secondary hydrothermal wood vinegar solution, hydrothermally reacting at 200-350° C. for 0.5-2 h, filtering to obtain the tertiary hydrothermal wood vinegar solution, and recovering the nickel oxide / calcium borate composite catalyst at the same time.
[0039] The present invention will be described in more detail below.
[0040] (1) using a crusher to crush the coarse biomass to a particle size of less than 0.2 mm to obtain biomass powder;
[0041] The purpose of pulverizing in this step is to allow the biomass to better mix and contact with water and the catalyst. If the biomass particle size is too large, it will cause incomplete pyrolysis during the hydrothermal process of the biomass.
[0042] (2) Dissolve Ni(NO3)2·6H2O in water to prepare a solution with a mass concentration of 10%, disperse CaO·B2O3·2H2O in the Ni(NO3)2·6H2O solution at a weight ratio of CaO·B2O3·2H2O to Ni(NO3)2·6H2O powder of 0.5-2:10, stir and disperse by ultrasonic, let stand for 3 h, dry in vacuum at 80°C for 10 h, calcine at 350°C under nitrogen protection for 3 h, grind, rinse with water, filter, and dry to obtain a NiO / CaO·B2O3 composite catalyst.
[0043] This step is to use the principle of co-precipitation to load Ni(NO3)2·6H2O on the acidic sites and pores of calcium borate when it precipitates, and after calcination, Ni(NO3)2 becomes NiO. This step gives the catalyst magnetism, and the catalyst can be recycled and reused after the hydrothermal treatment is completed. At the same time, the metal oxide NiO also has a certain catalytic effect on the pyrolysis of biomass.
[0044] In this step, the weight ratio of CaO·B2O3·2H2O to Ni(NO3)2·6H2O powder is controlled at 0.5-2:10. If the ratio is too low, the NiO content in the catalyst after calcination is too low, resulting in weak magnetism, which is not conducive to catalyst recovery. If the ratio is too high, the catalyst after calcination is doped with free NiO, resulting in waste.
[0045] (3) mixing the biomass powder in step (1) with the NiO / CaO·B2O3 composite catalyst obtained in step (2) at a weight ratio of 10:1-3, adding water at a weight ratio of 1:10-15 to the biomass powder, and stirring to obtain a biomass-catalyst-water suspension; transferring the obtained biomass-catalyst-water suspension to a high-pressure reactor, performing a hydrothermal reaction at a temperature of 200-350° C. and a heat preservation time of 0.5-2 h, cooling after the reaction, taking out the reaction product, vacuum filtering, and obtaining a filtrate, namely a first-grade hydrothermal wood vinegar liquid; using a magnet to recover and dry the NiO / CaO·B2O3 composite catalyst in the filter cake for reuse in subsequent reactions;
[0046] (4) adding the same amount of biomass and NiO / CaO·B2O3 composite catalyst as in step (3) to the first hydrothermal wood vinegar obtained in step (3), adding water so that the mass ratio of biomass powder to liquid is the same as in step (3), repeating the hydrothermal step of step (4) to obtain a second hydrothermal wood vinegar and a recovered composite catalyst;
[0047] (5) adding the same amount of biomass powder and the recovered composite catalyst as in step (3) to the secondary hydrothermal wood vinegar obtained in step (4), adding water so that the mass ratio of biomass powder to liquid is the same as in step (3), repeating the hydrothermal step of step (4) to obtain a tertiary hydrothermal wood vinegar;
[0048] In this step, if the reaction temperature is between 230 and 270°C, the insulation time is controlled between 1 and 2 hours to allow the biomass to be fully pyrolyzed; if the reaction temperature is between 270 and 350°C, the insulation time is controlled between 0.5 and 1 hour to prevent the hydrothermal time from being too long and decomposing the effective antibacterial components in the wood vinegar.
[0049] (6) The hydrothermal wood vinegar obtained in step (5) is stored in a dark and low temperature environment for 15 to 20 days, and after the wood vinegar is separated into layers, the middle aqueous phase is taken out to obtain a refined hydrothermal wood vinegar.
[0050] This step is the wood vinegar refining step, and its purpose is to separate the tar and some other harmful organic substances in the wood vinegar into heavy tar and light tar.
[0051] If the storage time is too short, the harmful substances in the wood vinegar will not be completely separated; if the storage time is too long, the wood vinegar will be over-oxidized during the storage process, causing its antibacterial properties to weaken.
[0052] A multi-stage catalytic hydrothermal wood vinegar liquid is prepared by the method.
[0053] The application of the above-mentioned multi-stage catalytic hydrothermal wood vinegar in the antibacterial field.
[0054] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0055] (1) The method for preparing wood vinegar has the characteristics of high yield and low content of harmful substances such as tar, and the refining process is simple, which reduces the cost of subsequent refining.
[0056] (2) The nickel oxide and calcium borate in the nickel oxide / calcium borate composite catalyst of the present invention have a synergistic effect, which can significantly increase the content of organic matter in the hydrothermal wood vinegar components, especially significantly increase the content of major antibacterial substances such as phenols and acids, and have more excellent antibacterial properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0057] Figure 1 The antibacterial properties of the wood vinegar obtained in Example 6 of the present invention against Staphylococcus aureus and Escherichia coli. DETAILED DESCRIPTION
[0058] The present invention is further described in detail below in conjunction with examples and drawings, but the embodiments of the present invention are not limited thereto.
[0059] If no specific conditions are specified in the examples of the present invention, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. All raw materials, reagents, etc., whose manufacturers are not specified, are conventional products that can be purchased commercially.
[0060] Example 1
[0061] Take 10g Ni(NO3)2·6H2O powder to prepare a solution with a mass concentration of 10%, take 1g CaO·B2O3·2H2O powder and disperse it into the prepared Ni(NO3)2·6H2O solution, stir for 20min and then ultrasonically disperse for 20min to completely disperse the CaO·B2O3·2H2O, let it stand for 3h, vacuum dry at 80℃ for 10h, calcine at 350℃ for 3h, grind, rinse with water, filter, and dry to obtain NiO / CaO·B2O3 composite catalyst powder.
[0062] The corn stalks were crushed by a crusher and passed through a 100 mesh sieve to obtain corn stalk powder with a particle size of less than 0.2 mm. 1 g of NiO / CaO·B2O3 composite catalyst powder and 10 g of the above corn stalk powder were added to 100 g of water, stirred evenly and transferred into a high-pressure reactor. The reactor was purged with nitrogen and sealed after detecting that there was no oxygen in the outlet air. The hydrothermal reaction was carried out at a temperature of 230°C and a holding time of 1 h. After the reaction was completed, the reactor was naturally cooled to room temperature. The reaction product was poured out and filtered to obtain a first-grade hydrothermal wood vinegar.
[0063] Add water to the first hydrothermal wood vinegar obtained above to 100g, then add 1g NiO / CaO·B2O3 composite catalyst powder and 10g corn stalk powder, repeat the above hydrothermal and filtration steps to obtain a second hydrothermal wood vinegar. Add water to the second hydrothermal wood vinegar obtained above to 100g, then add 1g NiO / CaO·B2O3 composite catalyst powder and 10g corn stalk powder, repeat the above hydrothermal and filtration steps to obtain a third hydrothermal wood vinegar. Then, after the third hydrothermal wood vinegar is stored at low temperature in the dark for 15 days, the crude wood vinegar is divided into 3 layers, the upper layer is a thin light oil phase layer, the middle is a liquid phase layer, and the lower part is a sedimentation tar layer. Take out the middle liquid phase layer to obtain a refined hydrothermal wood vinegar.
[0064] Example 2
[0065] Take 10g Ni(NO3)2·6H2O powder to prepare a solution with a mass concentration of 10%, take 1g CaO·B2O3·2H2O powder and disperse it into the prepared Ni(NO3)2·6H2O solution, stir for 20min and then ultrasonically disperse for 20min to completely disperse the CaO·B2O3·2H2O, let it stand for 3h, vacuum dry at 80℃ for 10h, calcine at 350℃ for 3h, grind, rinse with water, filter, and dry to obtain NiO / CaO·B2O3 composite catalyst powder.
[0066] The corn stalks were crushed by a crusher and passed through a 100 mesh sieve to obtain corn stalk powder with a particle size of less than 0.2 mm. 1 g of NiO / CaO·B2O3 composite catalyst powder and 10 g of the above corn stalk powder were added to 100 g of water, stirred evenly and transferred into a high-pressure reactor. The reactor was purged with nitrogen and sealed after detecting that there was no oxygen in the outlet air. The hydrothermal reaction was carried out at a temperature of 230°C and a holding time of 2 hours. After the reaction was completed, the reactor was naturally cooled to room temperature. The reaction product was poured out and filtered to obtain a first-grade hydrothermal wood vinegar.
[0067] Add water to the first hydrothermal wood vinegar obtained above to 100g, then add 1g NiO / CaO·B2O3 composite catalyst powder and 10g corn stalk powder, repeat the above hydrothermal and filtration steps to obtain a second hydrothermal wood vinegar. Add water to the second hydrothermal wood vinegar obtained above to 100g, then add 1g NiO / CaO·B2O3 composite catalyst powder and 10g corn stalk powder, repeat the above hydrothermal and filtration steps to obtain a third hydrothermal wood vinegar. Then, after the third hydrothermal wood vinegar is stored at low temperature in the dark for 15 days, the crude wood vinegar is divided into 3 layers, the upper layer is a thin light oil phase layer, the middle is a liquid phase layer, and the lower part is a sedimentation tar layer. Take out the middle liquid phase layer to obtain a refined hydrothermal wood vinegar.
[0068] Example 3
[0069] Take 10g Ni(NO3)2·6H2O powder to prepare a solution with a mass concentration of 10%, take 1g CaO·B2O3·2H2O powder and disperse it into the prepared Ni(NO3)2·6H2O solution, stir for 20min and then ultrasonically disperse for 20min to completely disperse the CaO·B2O3·2H2O, let it stand for 3h, vacuum dry at 80℃ for 10h, calcine at 350℃ for 3h, grind, rinse with water, filter, and dry to obtain NiO / CaO·B2O3 composite catalyst powder.
[0070] The corn stalks were crushed by a crusher and passed through a 100 mesh sieve to obtain corn stalk powder with a particle size of less than 0.2 mm. 1 g of NiO / CaO·B2O3 composite catalyst powder and 10 g of the above corn stalk powder were added to 100 g of water, stirred evenly and transferred into a high-pressure reactor. The reactor was purged with nitrogen and sealed after detecting that there was no oxygen in the outlet air. The hydrothermal reaction was carried out at a temperature of 260°C and a holding time of 2 hours. After the reaction was completed, the reactor was naturally cooled to room temperature. The reaction product was poured out and filtered to obtain a first-grade hydrothermal wood vinegar.
[0071] Add water to the first hydrothermal wood vinegar obtained above to 100g, then add 1g NiO / CaO·B2O3 composite catalyst powder and 10g corn stalk powder, repeat the above hydrothermal and filtration steps to obtain a second hydrothermal wood vinegar. Add water to the second hydrothermal wood vinegar obtained above to 100g, then add 1g NiO / CaO·B2O3 composite catalyst powder and 10g corn stalk powder, repeat the above hydrothermal and filtration steps to obtain a third hydrothermal wood vinegar. Then, after the third hydrothermal wood vinegar is stored at low temperature in the dark for 15 days, the crude wood vinegar is divided into 3 layers, the upper layer is a thin light oil phase layer, the middle is a liquid phase layer, and the lower part is a sedimentation tar layer. Take out the middle liquid phase layer to obtain a refined hydrothermal wood vinegar.
[0072] Example 4
[0073] Take 10g Ni(NO3)2·6H2O powder to prepare a solution with a mass concentration of 10%, take 1g CaO·B2O3·2H2O powder and disperse it into the prepared Ni(NO3)2·6H2O solution, stir for 20min and then ultrasonically disperse for 20min to completely disperse the CaO·B2O3·2H2O, let it stand for 3h, vacuum dry at 80℃ for 10h, calcine at 350℃ for 3h, grind, rinse with water, filter, and dry to obtain NiO / CaO·B2O3 composite catalyst powder.
[0074] The corn stalks were crushed by a crusher and passed through a 100 mesh sieve to obtain corn stalk powder with a particle size of less than 0.2 mm. 1 g of NiO / CaO·B2O3 composite catalyst powder and 10 g of the above corn stalk powder were added to 100 g of water, stirred evenly and transferred into a high-pressure reactor. The reactor was purged with nitrogen and sealed after detecting that there was no oxygen in the outlet air. The hydrothermal reaction was carried out at a temperature of 280°C and a holding time of 0.5 h. After the reaction was completed, the reactor was naturally cooled to room temperature. The reaction product was poured out and filtered to obtain a first-grade hydrothermal wood vinegar.
[0075] Add water to the first hydrothermal wood vinegar obtained above to 100g, then add 1g NiO / CaO·B2O3 composite catalyst powder and 10g corn stalk powder, repeat the above hydrothermal and filtration steps to obtain a second hydrothermal wood vinegar. Add water to the second hydrothermal wood vinegar obtained above to 100g, then add 1g NiO / CaO·B2O3 composite catalyst powder and 10g corn stalk powder, repeat the above hydrothermal and filtration steps to obtain a third hydrothermal wood vinegar. Then, after the third hydrothermal wood vinegar is stored at low temperature in the dark for 15 days, the crude wood vinegar is divided into 3 layers, the upper layer is a thin light oil phase layer, the middle is a liquid phase layer, and the lower part is a sedimentation tar layer. Take out the middle liquid phase layer to obtain a refined hydrothermal wood vinegar.
[0076] Example 5
[0077] Take 10g Ni(NO3)2·6H2O powder to prepare a solution with a mass concentration of 10%, take 1g CaO·B2O3·2H2O powder and disperse it into the prepared Ni(NO3)2·6H2O solution, stir for 20min and then ultrasonically disperse for 20min to completely disperse the CaO·B2O3·2H2O, let it stand for 3h, vacuum dry at 80℃ for 10h, calcine at 350℃ for 3h, grind, rinse with water, filter, and dry to obtain NiO / CaO·B2O3 composite catalyst powder.
[0078] The corn stalks were crushed by a crusher and passed through a 100 mesh sieve to obtain corn stalk powder with a particle size of less than 0.2 mm. 1 g of NiO / CaO·B2O3 composite catalyst powder and 10 g of the above corn stalk powder were added to 100 g of water, stirred evenly and transferred into a high-pressure reactor. The high-pressure reactor was purged with nitrogen, and the reactor was sealed after detecting that there was no oxygen in the outlet air. The hydrothermal reaction was carried out at a temperature of 280°C and a holding time of 1 h. After the reaction was completed, the reactor was naturally cooled to room temperature. The reaction product was poured out and filtered to obtain a first-grade hydrothermal wood vinegar.
[0079] Add water to the first hydrothermal wood vinegar obtained above to 100g, then add 1g NiO / CaO·B2O3 composite catalyst powder and 10g corn stalk powder, repeat the above hydrothermal and filtration steps to obtain a second hydrothermal wood vinegar. Add water to the second hydrothermal wood vinegar obtained above to 100g, then add 1g NiO / CaO·B2O3 composite catalyst powder and 10g corn stalk powder, repeat the above hydrothermal and filtration steps to obtain a third hydrothermal wood vinegar. Then, after the third hydrothermal wood vinegar is stored at low temperature in the dark for 15 days, the crude wood vinegar is divided into 3 layers, the upper layer is a thin light oil phase layer, the middle is a liquid phase layer, and the lower part is a sedimentation tar layer. Take out the middle liquid phase layer to obtain a refined hydrothermal wood vinegar.
[0080] Example 6
[0081] Take 10g Ni(NO3)2·6H2O powder to prepare a solution with a mass concentration of 10%, take 1g CaO·B2O3·2H2O powder and disperse it into the prepared Ni(NO3)2·6H2O solution, stir for 20min and then ultrasonically disperse for 20min to completely disperse the CaO·B2O3·2H2O, let it stand for 3h, vacuum dry at 80℃ for 10h, calcine at 350℃ for 3h, grind, rinse with water, filter, and dry to obtain NiO / CaO·B2O3 composite catalyst powder.
[0082] The corn stalks were crushed by a crusher and passed through a 100 mesh sieve to obtain corn stalk powder with a particle size of less than 0.2 mm. 1 g of NiO / CaO·B2O3 composite catalyst powder and 10 g of the above corn stalk powder were added to 100 g of water, stirred evenly and transferred into a high-pressure reactor. The reactor was purged with nitrogen and sealed after detecting that there was no oxygen in the outlet air. The hydrothermal reaction was carried out at a temperature of 280°C and a holding time of 2 hours. After the reaction was completed, the reactor was naturally cooled to room temperature. The reaction product was poured out and filtered to obtain a first-grade hydrothermal wood vinegar.
[0083] Add water to the first hydrothermal wood vinegar obtained above to 100g, then add 1g NiO / CaO·B2O3 composite catalyst powder and 10g corn stalk powder, repeat the above hydrothermal and filtration steps to obtain a second hydrothermal wood vinegar. Add water to the second hydrothermal wood vinegar obtained above to 100g, then add 1g NiO / CaO·B2O3 composite catalyst powder and 10g corn stalk powder, repeat the above hydrothermal and filtration steps to obtain a third hydrothermal wood vinegar. Then, after the third hydrothermal wood vinegar is stored at low temperature in the dark for 15 days, the crude wood vinegar is divided into 3 layers, the upper layer is a thin light oil phase layer, the middle is a liquid phase layer, and the lower part is a sedimentation tar layer. Take out the middle liquid phase layer to obtain a refined hydrothermal wood vinegar.
[0084] Example 7
[0085] Take 10g Ni(NO3)2·6H2O powder to prepare a solution with a mass concentration of 10%, take 1g CaO·B2O3·2H2O powder and disperse it into the prepared Ni(NO3)2·6H2O solution, stir for 20min and then ultrasonically disperse for 20min to completely disperse the CaO·B2O3·2H2O, let it stand for 3h, vacuum dry at 80℃ for 10h, calcine at 350℃ for 3h, grind, rinse with water, filter, and dry to obtain NiO / CaO·B2O3 composite catalyst powder.
[0086] The corn stalks were crushed by a crusher and passed through a 100 mesh sieve to obtain corn stalk powder with a particle size of less than 0.2 mm. 1 g of NiO / CaO·B2O3 composite catalyst powder and 10 g of the above corn stalk powder were added to 100 g of water, stirred evenly and transferred into a high-pressure reactor. The reactor was purged with nitrogen and sealed after detecting that there was no oxygen in the outlet air. The hydrothermal reaction was carried out at a temperature of 300°C and a holding time of 2 hours. After the reaction was completed, the reactor was naturally cooled to room temperature. The reaction product was poured out and filtered to obtain a first-grade hydrothermal wood vinegar.
[0087] Add water to the first hydrothermal wood vinegar obtained above to 100g, then add 1g NiO / CaO·B2O3 composite catalyst powder and 10g corn stalk powder, repeat the above hydrothermal and filtration steps to obtain a second hydrothermal wood vinegar. Add water to the second hydrothermal wood vinegar obtained above to 100g, then add 1g NiO / CaO·B2O3 composite catalyst powder and 10g corn stalk powder, repeat the above hydrothermal and filtration steps to obtain a third hydrothermal wood vinegar. Then, after the third hydrothermal wood vinegar is stored at low temperature in the dark for 15 days, the crude wood vinegar is divided into 3 layers, the upper layer is a thin light oil phase layer, the middle is a liquid phase layer, and the lower part is a sedimentation tar layer. Take out the middle liquid phase layer to obtain a refined hydrothermal wood vinegar.
[0088] Example 8
[0089] Take 10g Ni(NO3)2·6H2O powder to prepare a solution with a mass concentration of 10%, take 1g CaO·B2O3·2H2O powder and disperse it into the prepared Ni(NO3)2·6H2O solution, stir for 20min and then ultrasonically disperse for 20min to completely disperse the CaO·B2O3·2H2O, let it stand for 3h, vacuum dry at 80℃ for 10h, calcine at 350℃ for 3h, grind, rinse with water, filter, and dry to obtain NiO / CaO·B2O3 composite catalyst powder.
[0090] The corn stalks were crushed by a crusher and passed through a 100 mesh sieve to obtain corn stalk powder with a particle size of less than 0.2 mm. 3 g of NiO / CaO·B2O3 composite catalyst powder and 10 g of the above corn stalk powder were added to 100 g of water, stirred evenly and transferred into a high-pressure reactor. The reactor was purged with nitrogen and sealed after detecting that there was no oxygen in the outlet air. The hydrothermal reaction was carried out at a temperature of 280°C and a holding time of 2 hours. After the reaction was completed, the reactor was naturally cooled to room temperature. The reaction product was poured out and filtered to obtain a first-grade hydrothermal wood vinegar.
[0091] Add water to the first hydrothermal wood vinegar obtained above to 100g, then add 3g NiO / CaO·B2O3 composite catalyst powder and 10g corn stalk powder, repeat the above hydrothermal and filtration steps to obtain a second hydrothermal wood vinegar. Add water to the second hydrothermal wood vinegar obtained above to 100g, then add 3g NiO / CaO·B2O3 composite catalyst powder and 10g corn stalk powder, repeat the above hydrothermal and filtration steps to obtain a third hydrothermal wood vinegar. Then, the third hydrothermal wood vinegar is stored at low temperature in the dark for 15 days, and the crude wood vinegar is divided into 3 layers, the upper layer is a thin light oil phase layer, the middle is a liquid phase layer, and the lower part is a sedimentation tar layer. Take out the middle liquid phase layer to obtain a refined hydrothermal wood vinegar.
[0092] Example 9
[0093] Take 10g Ni(NO3)2·6H2O powder to prepare a solution with a mass concentration of 10%, take 1g CaO·B2O3·2H2O powder and disperse it into the prepared Ni(NO3)2·6H2O solution, stir for 20min and then ultrasonically disperse for 20min to completely disperse the CaO·B2O3·2H2O, let it stand for 3h, vacuum dry at 80℃ for 10h, calcine at 350℃ for 3h, grind, rinse with water, filter, and dry to obtain NiO / CaO·B2O3 composite catalyst powder.
[0094] The corn stalks were crushed by a crusher and passed through a 100 mesh sieve to obtain corn stalk powder with a particle size of less than 0.2 mm. 1g of NiO / CaO·B2O3 composite catalyst powder and 10g of the above corn stalk powder were added to 150g of water, stirred evenly and transferred into a high-pressure reactor. The reactor was purged with nitrogen and sealed after detecting that there was no oxygen in the outlet air. The hydrothermal reaction was carried out at a temperature of 280°C and a holding time of 2h. After the reaction was completed, the reactor was naturally cooled to room temperature. The reaction product was poured out and filtered to obtain a first-grade hydrothermal wood vinegar.
[0095] Add water to the first hydrothermal wood vinegar obtained above to 150g, then add 1g NiO / CaO·B2O3 composite catalyst powder and 10g corn stalk powder, repeat the above hydrothermal and filtration steps to obtain a second hydrothermal wood vinegar. Add water to the second hydrothermal wood vinegar obtained above to 150g, then add 1g NiO / CaO·B2O3 composite catalyst powder and 10g corn stalk powder, repeat the above hydrothermal and filtration steps to obtain a third hydrothermal wood vinegar. Then, after the third hydrothermal wood vinegar is stored at low temperature in the dark for 15 days, the crude wood vinegar is divided into 3 layers, the upper layer is a thin light oil phase layer, the middle is a liquid phase layer, and the lower part is a sedimentation tar layer. Take out the middle liquid phase layer to obtain a refined hydrothermal wood vinegar.
[0096] Example 10
[0097] Take 10g Ni(NO3)2·6H2O powder to prepare a solution with a mass concentration of 10%, take 1g CaO·B2O3·2H2O powder and disperse it into the prepared Ni(NO3)2·6H2O solution, stir for 20min and then ultrasonically disperse for 20min to completely disperse the CaO·B2O3·2H2O, let it stand for 3h, vacuum dry at 80℃ for 10h, calcine at 350℃ for 3h, grind, rinse with water, filter, and dry to obtain NiO / CaO·B2O3 composite catalyst powder.
[0098] The corn stalks were crushed by a crusher and passed through a 100 mesh sieve to obtain corn stalk powder with a particle size of less than 0.2 mm. 1 g of NiO / CaO·B2O3 composite catalyst powder and 10 g of the above corn stalk powder were added to 200 g of water, stirred evenly and transferred into a high-pressure reactor. The reactor was purged with nitrogen and sealed after detecting that there was no oxygen in the outlet air. The hydrothermal reaction was carried out at a temperature of 280°C and a holding time of 2 hours. After the reaction was completed, the reactor was naturally cooled to room temperature. The reaction product was poured out and filtered to obtain a first-grade hydrothermal wood vinegar.
[0099] Add water to the first hydrothermal wood vinegar obtained above to 200g, then add 1g NiO / CaO·B2O3 composite catalyst powder and 10g corn stalk powder, repeat the above hydrothermal and filtration steps to obtain a second hydrothermal wood vinegar. Add water to the second hydrothermal wood vinegar obtained above to 200g, then add 1g NiO / CaO·B2O3 composite catalyst powder and 10g corn stalk powder, repeat the above hydrothermal and filtration steps to obtain a third hydrothermal wood vinegar. Then, after the third hydrothermal wood vinegar is stored at low temperature in the dark for 15 days, the crude wood vinegar is divided into 3 layers, the upper layer is a thin light oil phase layer, the middle is a liquid phase layer, and the lower part is a sedimentation tar layer. Take out the middle liquid phase layer to obtain a refined hydrothermal wood vinegar.
[0100] Embodiment 11
[0101] Take 10g Ni(NO3)2·6H2O powder to prepare a solution with a mass concentration of 10%, take 1g CaO·B2O3·2H2O powder and disperse it into the prepared Ni(NO3)2·6H2O solution, stir for 20min and then ultrasonically disperse for 20min to completely disperse the CaO·B2O3·2H2O, let it stand for 3h, vacuum dry at 80℃ for 10h, calcine at 350℃ for 3h, grind, rinse with water, filter, and dry to obtain NiO / CaO·B2O3 composite catalyst powder.
[0102] The corn stalks were crushed by a crusher and passed through a 100 mesh sieve to obtain corn stalk powder with a particle size of less than 0.2 mm. 1 g of NiO / CaO·B2O3 composite catalyst powder and 10 g of the above corn stalk powder were added to 100 g of water, stirred evenly and transferred into a high-pressure reactor. The reactor was purged with nitrogen and sealed after detecting that there was no oxygen in the outlet air. The hydrothermal reaction was carried out at a temperature of 200°C and a holding time of 2 hours. After the reaction was completed, the reactor was naturally cooled to room temperature. The reaction product was poured out and filtered to obtain a first-grade hydrothermal wood vinegar.
[0103] Add water to the first hydrothermal wood vinegar obtained above to 100g, then add 1g NiO / CaO·B2O3 composite catalyst powder and 10g corn stalk powder, repeat the above hydrothermal and filtration steps to obtain a second hydrothermal wood vinegar. Add water to the second hydrothermal wood vinegar obtained above to 100g, then add 1g NiO / CaO·B2O3 composite catalyst powder and 10g corn stalk powder, repeat the above hydrothermal and filtration steps to obtain a third hydrothermal wood vinegar. Then, after the third hydrothermal wood vinegar is stored at low temperature in the dark for 15 days, the crude wood vinegar is divided into 3 layers, the upper layer is a thin light oil phase layer, the middle is a liquid phase layer, and the lower part is a sedimentation tar layer. Take out the middle liquid phase layer to obtain a refined hydrothermal wood vinegar.
[0104] Example 12
[0105] Take 10g Ni(NO3)2·6H2O powder to prepare a solution with a mass concentration of 10%, take 1g CaO·B2O3·2H2O powder and disperse it into the prepared Ni(NO3)2·6H2O solution, stir for 20min and then ultrasonically disperse for 20min to completely disperse the CaO·B2O3·2H2O, let it stand for 3h, vacuum dry at 80℃ for 10h, calcine at 350℃ for 3h, grind, rinse with water, filter, and dry to obtain NiO / CaO·B2O3 composite catalyst powder.
[0106] The corn stalks were crushed by a crusher and passed through a 100 mesh sieve to obtain corn stalk powder with a particle size of less than 0.2 mm. 1 g of NiO / CaO·B2O3 composite catalyst powder and 10 g of the above corn stalk powder were added to 100 g of water, stirred evenly and transferred into a high-pressure reactor. The reactor was purged with nitrogen and sealed after detecting that there was no oxygen in the outlet air. The hydrothermal reaction was carried out at a temperature of 350°C and a holding time of 2 hours. After the reaction was completed, the reactor was naturally cooled to room temperature. The reaction product was poured out and filtered to obtain a first-grade hydrothermal wood vinegar.
[0107] Add water to the first hydrothermal wood vinegar obtained above to 100g, then add 1g NiO / CaO·B2O3 composite catalyst powder and 10g corn stalk powder, repeat the above hydrothermal and filtration steps to obtain a second hydrothermal wood vinegar. Add water to the second hydrothermal wood vinegar obtained above to 100g, then add 1g NiO / CaO·B2O3 composite catalyst powder and 10g corn stalk powder, repeat the above hydrothermal and filtration steps to obtain a third hydrothermal wood vinegar. Then, after the third hydrothermal wood vinegar is stored at low temperature in the dark for 15 days, the crude wood vinegar is divided into 3 layers, the upper layer is a thin light oil phase layer, the middle is a liquid phase layer, and the lower part is a sedimentation tar layer. Take out the middle liquid phase layer to obtain a refined hydrothermal wood vinegar.
[0108] Example 13
[0109] Take 10g Ni(NO3)2·6H2O powder to prepare a solution with a mass concentration of 10%, take 1g CaO·B2O3·2H2O powder and disperse it into the prepared Ni(NO3)2·6H2O solution, stir for 20min and then ultrasonically disperse for 20min to completely disperse the CaO·B2O3·2H2O, let it stand for 3h, vacuum dry at 80℃ for 10h, calcine at 350℃ for 3h, grind, rinse with water, filter, and dry to obtain NiO / CaO·B2O3 composite catalyst powder.
[0110] The bagasse is crushed by a crusher and passed through a 100-mesh sieve to obtain bagasse powder with a particle size of less than 0.2 mm. 1 g of NiO / CaO·B2O3 composite catalyst powder and 10 g of the above bagasse powder are added to 100 g of water, stirred evenly and transferred into a high-pressure reactor. The reactor is purged with nitrogen and sealed after detecting that there is no oxygen in the outlet air. The hydrothermal reaction is carried out at a temperature of 280°C and a holding time of 2 hours. After the reaction is completed, the reactor is allowed to cool naturally to room temperature. The reaction product is poured out and filtered to obtain a first-grade hydrothermal wood vinegar.
[0111] Add water to the first hydrothermal wood vinegar obtained above to 100g, then add 1g NiO / CaO·B2O3 composite catalyst powder and 10g bagasse powder, repeat the above hydrothermal and filtration steps to obtain a second hydrothermal wood vinegar. Add water to the second hydrothermal wood vinegar obtained above to 100g, then add 1g NiO / CaO·B2O3 composite catalyst powder and 10g bagasse powder, repeat the above hydrothermal and filtration steps to obtain a third hydrothermal wood vinegar. Then, the third hydrothermal wood vinegar is stored at low temperature in the dark for 15 days, and the crude wood vinegar is divided into 3 layers, the upper layer is a thin light oil phase layer, the middle is a liquid phase layer, and the lower part is a sedimentation tar layer. Take out the middle liquid phase layer to obtain a refined hydrothermal wood vinegar.
[0112] Embodiment 14
[0113] Take 10g Ni(NO3)2·6H2O powder to prepare a solution with a mass concentration of 10%, take 1g CaO·B2O3·2H2O powder and disperse it into the prepared Ni(NO3)2·6H2O solution, stir for 20min and then ultrasonically disperse for 20min to completely disperse the CaO·B2O3·2H2O, let it stand for 3h, vacuum dry at 80℃ for 10h, calcine at 350℃ for 3h, grind, rinse with water, filter, and dry to obtain NiO / CaO·B2O3 composite catalyst powder.
[0114] The bamboo is crushed by a crusher and passed through a 100-mesh sieve to obtain bamboo powder with a particle size of less than 0.2 mm. 1 g of NiO / CaO·B2O3 composite catalyst powder and 10 g of the above-mentioned bamboo powder are added to 100 g of water, stirred evenly and transferred into a high-pressure reactor. The reactor is purged with nitrogen, and the reactor is sealed after detecting that there is no oxygen in the outlet air. The hydrothermal reaction is carried out at a temperature of 280°C and a heat preservation time of 2 hours. After the reaction is completed, the reactor is naturally cooled to room temperature. The reaction product is poured out and filtered to obtain a first-grade hydrothermal wood vinegar.
[0115] Add water to the first hydrothermal wood vinegar obtained above to 100g, then add 1g NiO / CaO·B2O3 composite catalyst powder and 10g bamboo powder, repeat the above hydrothermal and filtration steps to obtain a second hydrothermal wood vinegar. Add water to the second hydrothermal wood vinegar obtained above to 100g, then add 1g NiO / CaO·B2O3 composite catalyst powder and 10g bamboo powder, repeat the above hydrothermal and filtration steps to obtain a third hydrothermal wood vinegar. Then, the third hydrothermal wood vinegar is stored at low temperature in the dark for 15 days, and the crude wood vinegar is divided into 3 layers, the upper layer is a thin light oil phase layer, the middle is a liquid phase layer, and the lower part is a sedimentation tar layer. Take out the middle liquid phase layer to obtain a refined hydrothermal wood vinegar.
[0116] Embodiment 15
[0117] Take 10g Ni(NO3)2·6H2O powder to prepare a solution with a mass concentration of 10%, take 1g CaO·B2O3·2H2O powder and disperse it into the prepared Ni(NO3)2·6H2O solution, stir for 20min and then ultrasonically disperse for 20min to completely disperse the CaO·B2O3·2H2O, let it stand for 3h, vacuum dry at 80℃ for 10h, calcine at 350℃ for 3h, grind, rinse with water, filter, and dry to obtain NiO / CaO·B2O3 composite catalyst powder.
[0118] The corn stalks were crushed by a crusher and passed through a 100 mesh sieve to obtain corn stalk powder with a particle size of less than 0.2 mm. 1g of NiO / CaO·B2O3 composite catalyst powder and 10g of the above corn stalk powder were added to 120g of water, stirred evenly and transferred into a high-pressure reactor. The reactor was purged with nitrogen and sealed after detecting that there was no oxygen in the outlet air. The hydrothermal reaction was carried out at a temperature of 280°C and a holding time of 2h. After the reaction was completed, the reactor was naturally cooled to room temperature. The reaction product was poured out and filtered to obtain a first-grade hydrothermal wood vinegar.
[0119] Add water to the first hydrothermal wood vinegar obtained above to 120g, then add 1g NiO / CaO·B2O3 composite catalyst powder and 10g corn stalk powder, repeat the above hydrothermal and filtration steps to obtain a second hydrothermal wood vinegar. Add water to the second hydrothermal wood vinegar obtained above to 120g, then add 1g NiO / CaO·B2O3 composite catalyst powder and 10g corn stalk powder, repeat the above hydrothermal and filtration steps to obtain a third hydrothermal wood vinegar. Then, after the third hydrothermal wood vinegar is stored at low temperature in the dark for 15 days, the crude wood vinegar is divided into 3 layers, the upper layer is a thin light oil phase layer, the middle is a liquid phase layer, and the lower part is a sedimentation tar layer. Take out the middle liquid phase layer to obtain a refined hydrothermal wood vinegar.
[0120] Example 16
[0121] Take 10g Ni(NO3)2·6H2O powder to prepare a solution with a mass concentration of 10%, take 1g CaO·B2O3·2H2O powder and disperse it into the prepared Ni(NO3)2·6H2O solution, stir for 20min and then ultrasonically disperse for 20min to completely disperse the CaO·B2O3·2H2O, let it stand for 3h, vacuum dry at 80℃ for 10h, calcine at 350℃ for 3h, grind, rinse with water, filter, and dry to obtain NiO / CaO·B2O3 composite catalyst powder.
[0122] The corn stalks were crushed by a crusher and passed through a 100 mesh sieve to obtain corn stalk powder with a particle size of less than 0.2 mm. 1 g of NiO / CaO·B2O3 composite catalyst powder and 10 g of the above corn stalk powder were added to 100 g of water, stirred evenly and transferred into a high-pressure reactor. The reactor was purged with nitrogen and sealed after detecting that there was no oxygen in the outlet air. The hydrothermal reaction was carried out at a temperature of 280°C and a holding time of 2 hours. After the reaction was completed, the reactor was naturally cooled to room temperature. The reaction product was poured out and filtered to obtain a first-grade hydrothermal wood vinegar.
[0123] Add water to the first hydrothermal wood vinegar obtained above to 100g, then add 1g NiO / CaO·B2O3 composite catalyst powder and 10g corn stalk powder, repeat the above hydrothermal and filtration steps to obtain a second hydrothermal wood vinegar. Add water to the second hydrothermal wood vinegar obtained above to 100g, then add 1g NiO / CaO·B2O3 composite catalyst powder and 10g corn stalk powder, repeat the above hydrothermal and filtration steps to obtain a third hydrothermal wood vinegar. Then, after the third hydrothermal wood vinegar is stored at low temperature in the dark for 20 days, the crude wood vinegar is divided into 3 layers, the upper layer is a thin light oil phase layer, the middle is a liquid phase layer, and the lower part is a sedimentation tar layer. Take out the middle liquid phase layer to obtain a refined hydrothermal wood vinegar.
[0124] Embodiment 17
[0125] Take 10g Ni(NO3)2·6H2O powder to prepare a solution with a mass concentration of 10%, take 0.5g CaO·B2O3·2H2O powder and disperse it into the prepared Ni(NO3)2·6H2O solution, stir for 20min and then ultrasonically disperse for 20min to completely disperse the CaO·B2O3·2H2O, let it stand for 3h, vacuum dry at 80℃ for 10h, calcine at 350℃ for 3h, grind, rinse with water, filter, and dry to obtain NiO / CaO·B2O3 composite catalyst powder.
[0126] The corn stalks were crushed by a crusher and passed through a 100 mesh sieve to obtain corn stalk powder with a particle size of less than 0.2 mm. 1 g of NiO / CaO·B2O3 composite catalyst powder and 10 g of the above corn stalk powder were added to 100 g of water, stirred evenly and transferred into a high-pressure reactor. The reactor was purged with nitrogen and sealed after detecting that there was no oxygen in the outlet air. The hydrothermal reaction was carried out at a temperature of 280°C and a holding time of 2 hours. After the reaction was completed, the reactor was naturally cooled to room temperature. The reaction product was poured out and filtered to obtain a first-grade hydrothermal wood vinegar.
[0127] Add water to the first hydrothermal wood vinegar obtained above to 100g, then add 1g NiO / CaO·B2O3 composite catalyst powder and 10g corn stalk powder, repeat the above hydrothermal and filtration steps to obtain a second hydrothermal wood vinegar. Add water to the second hydrothermal wood vinegar obtained above to 100g, then add 1g NiO / CaO·B2O3 composite catalyst powder and 10g corn stalk powder, repeat the above hydrothermal and filtration steps to obtain a third hydrothermal wood vinegar. Then, after the third hydrothermal wood vinegar is stored at low temperature in the dark for 15 days, the crude wood vinegar is divided into 3 layers, the upper layer is a thin light oil phase layer, the middle is a liquid phase layer, and the lower part is a sedimentation tar layer. Take out the middle liquid phase layer to obtain a refined hydrothermal wood vinegar.
[0128] Embodiment 18
[0129] Take 10g Ni(NO3)2·6H2O powder to prepare a solution with a mass concentration of 10%, take 2g CaO·B2O3·2H2O powder and disperse it in the prepared Ni(NO3)2·6H2O solution, stir for 20min and then ultrasonically disperse for 20min to completely disperse the CaO·B2O3·2H2O, let it stand for 3h, vacuum dry at 80℃ for 10h, calcine at 350℃ for 3h, grind, rinse with water, filter, and dry to obtain NiO / CaO·B2O3 composite catalyst powder.
[0130] The corn stalks were crushed by a crusher and passed through a 100 mesh sieve to obtain corn stalk powder with a particle size of less than 0.2 mm. 1 g of NiO / CaO·B2O3 composite catalyst powder and 10 g of the above corn stalk powder were added to 100 g of water, stirred evenly and transferred into a high-pressure reactor. The reactor was purged with nitrogen and sealed after detecting that there was no oxygen in the outlet air. The hydrothermal reaction was carried out at a temperature of 280°C and a holding time of 2 hours. After the reaction was completed, the reactor was naturally cooled to room temperature. The reaction product was poured out and filtered to obtain a first-grade hydrothermal wood vinegar.
[0131] Add water to the first hydrothermal wood vinegar obtained above to 100g, then add 1g NiO / CaO·B2O3 composite catalyst powder and 10g corn stalk powder, repeat the above hydrothermal and filtration steps to obtain a second hydrothermal wood vinegar. Add water to the second hydrothermal wood vinegar obtained above to 100g, then add 1g NiO / CaO·B2O3 composite catalyst powder and 10g corn stalk powder, repeat the above hydrothermal and filtration steps to obtain a third hydrothermal wood vinegar. Then, after the third hydrothermal wood vinegar is stored at low temperature in the dark for 15 days, the crude wood vinegar is divided into 3 layers, the upper layer is a thin light oil phase layer, the middle is a liquid phase layer, and the lower part is a sedimentation tar layer. Take out the middle liquid phase layer to obtain a refined hydrothermal wood vinegar.
[0132] Embodiment 19
[0133] Take 10g Ni(NO3)2·6H2O powder to prepare a solution with a mass concentration of 10%, take 1g CaO·B2O3·2H2O powder and disperse it into the prepared Ni(NO3)2·6H2O solution, stir for 20min and then ultrasonically disperse for 20min to completely disperse the CaO·B2O3·2H2O, let it stand for 3h, vacuum dry at 80℃ for 10h, calcine at 350℃ for 3h, grind, rinse with water, filter, and dry to obtain NiO / CaO·B2O3 composite catalyst powder.
[0134] The corn stalks were crushed by a crusher and passed through a 100 mesh sieve to obtain corn stalk powder with a particle size of less than 0.2 mm. 1 g of NiO / CaO·B2O3 composite catalyst powder and 10 g of the above corn stalk powder were added to 100 g of water, stirred evenly and transferred into a high-pressure reactor. The reactor was purged with nitrogen and sealed after detecting that there was no oxygen in the outlet air. The hydrothermal reaction was carried out at a temperature of 280°C and a holding time of 2 hours. After the reaction was completed, the reactor was naturally cooled to room temperature. The reaction product was poured out and filtered to obtain a first-grade hydrothermal wood vinegar.
[0135] Add water to the first hydrothermal wood vinegar obtained above to 100g, then add 1g NiO / CaO·B2O3 composite catalyst powder and 10g corn straw powder, repeat the above hydrothermal and filtration steps to obtain a second hydrothermal wood vinegar. Add water to the second hydrothermal wood vinegar obtained above to 100g, then add 1g NiO / CaO·B2O3 composite catalyst powder and 10g corn straw powder, repeat the above hydrothermal and filtration steps to obtain a third hydrothermal wood vinegar. Add water to the third hydrothermal wood vinegar obtained above to 100g, then add 1g NiO / CaO·B2O3 composite catalyst powder and 10g corn straw powder, repeat the above hydrothermal and filtration steps to obtain a fourth hydrothermal wood vinegar. Then the fourth-level wood vinegar is stored in the dark and low temperature for 15 days, and the crude wood vinegar is divided into 3 layers, the upper layer is a thin light oil phase layer, the middle is a liquid phase layer, and the lower part is a sedimentation tar layer. The middle liquid phase layer is taken out to obtain refined hydrothermal wood vinegar.
[0136] Example Effect Description
[0137] The wood vinegar prepared in Examples 1 to 16 was characterized and its antibacterial properties were tested. The results are shown in Table 1.
[0138] The components of the wood vinegar samples were characterized by GC-MS, the TOC measuring instrument was used to characterize the total carbon content in the wood vinegar samples, the handheld pH agent was used to characterize the pH value of the wood vinegar, and the Baume density meter was used to characterize the density of the wood vinegar.
[0139] The viable bacteria counting method was used to evaluate the antibacterial properties of the wood vinegar prepared in the embodiment, and the bacteria used were Gram-positive bacteria Staphylococcus aureus (ATCC6538). Staphylococcus aureus was inoculated in LB medium and cultured at 37°C for 4 to 5 hours until the OD value was approximately equal to 1. It was contacted with the wood vinegar prepared in the embodiment in a 1:1 manner in a clean bench, and evenly coated on the LB solid culture medium after appropriate dilution. After culturing at 37°C in a constant temperature oven for 12 to 16 hours, the number of colonies on the solid culture medium was counted. The number of viable colonies on the blank group plate was recorded as C0, and the number of viable colonies on the experimental group plate was recorded as C1. The antibacterial ability calculation formula of the embodiment is:
[0140] R = log (C0*a-C1*b)
[0141] Wherein R is the logarithmic value of the bactericidal number of wood vinegar, a is the dilution multiple of the blank group, and b is the dilution multiple of the experimental group. The antibacterial properties of the embodiments are listed in Table 1.
[0142] Comparative Example 1 (Preparation of Wood Vinegar by Direct Hydrothermal Method)
[0143] The wood vinegar was prepared by the hydrothermal method used in patent application CN106590717.
[0144] The corn stalks were crushed by a crusher and passed through a 100-mesh sieve to obtain corn stalk powder. 10 g of corn stalk powder was added to 100 g of deionized water, stirred evenly, and the powder was fully moistened with water and then transferred into a high-pressure reactor for hydrothermal reaction at a temperature of 280 ° C and a heat preservation time of 2 h. After the reaction was completed, the reactor was naturally cooled to room temperature. The reaction product was poured out and filtered to obtain a crude hydrothermal wood vinegar. After the crude wood vinegar was stored at low temperature in the dark for 15 days, the crude wood vinegar was divided into 3 layers, the upper layer was a thin light oil phase layer, the middle layer was a liquid phase layer, and the lower layer was a sedimentation tar layer. The middle liquid phase layer was taken out to obtain a refined hydrothermal wood vinegar.
[0145] Comparative Example 2 (Preparation of Wood Vinegar by Hydrothermal Oxidation)
[0146] The wood vinegar was prepared by the hydrothermal method used in patent application CN106753501.
[0147] The corn stalks were crushed by a crusher, and then the corn stalk powder was collected and stored after being sieved through a 100-mesh sieve. 10 g of corn stalk powder was added to 100 g of a 6% hydrogen peroxide solution, stirred evenly, and the powder was fully moistened with water and then transferred to a high-pressure reactor. The reactor was purged with nitrogen, and the reactor was sealed after detecting that there was no oxygen in the outlet air. The hydrothermal reaction was carried out at a temperature of 280 ° C and a holding time of 2 h. After the reaction was completed, the reactor was allowed to cool naturally to room temperature. The reaction product was poured out and filtered to obtain a crude hydrothermal wood vinegar. After the crude wood vinegar was stored at low temperature in the dark for 15 days, the crude wood vinegar was divided into 3 layers, the upper layer was a thin light oil phase layer, the middle layer was a liquid phase layer, and the lower layer was a sedimentation tar layer. The middle liquid phase layer was taken out to obtain a refined hydrothermal wood vinegar.
[0148] Comparative Example 3 (no catalyst, three-stage hydrothermal)
[0149] The corn stalks were crushed by a crusher and passed through a 100 mesh sieve to obtain corn stalk powder with a particle size of less than 0.2 mm. 10 g of the corn stalk powder was added to 100 g of water, stirred evenly and transferred into a high-pressure reactor. The reactor was purged with nitrogen and sealed after detecting that there was no oxygen in the outlet air. The hydrothermal reaction was carried out at a temperature of 280 ° C and a heat preservation time of 2 hours. After the reaction was completed, the reactor was allowed to cool naturally to room temperature. The reaction product was poured out and filtered to obtain a first-grade hydrothermal wood vinegar.
[0150] In the first-level hydrothermal wood vinegar obtained above, water is added to 100g, and then 10g corn straw powder is added, and the above hydrothermal and filtering steps are repeated to obtain a second-level hydrothermal wood vinegar. In the second-level hydrothermal wood vinegar obtained above, water is added to 100g, and then 1g corn straw powder is added, and the above hydrothermal and filtering steps are repeated to obtain a third-level hydrothermal wood vinegar. Then the third-level wood vinegar is stored at low temperature in the dark for 15 days, and the crude wood vinegar is divided into 3 layers, the upper layer is a thin light oil phase layer, the middle is a liquid phase layer, and the lower part is a sedimentation tar layer. Take out the middle liquid phase layer to obtain a refined hydrothermal wood vinegar.
[0151] Comparative Example 4 (composite catalyst + primary hydrothermal)
[0152] Take 10g Ni(NO3)2·6H2O powder to prepare a solution with a mass concentration of 10%, take 1g CaO·B2O3·2H2O powder and disperse it into the prepared Ni(NO3)2·6H2O solution, stir for 20min and then ultrasonically disperse for 20min to completely disperse the CaO·B2O3·2H2O, let it stand for 3h, vacuum dry at 80℃ for 10h, calcine at 350℃ for 3h, grind, rinse with water, filter, and dry to obtain NiO / CaO·B2O3 composite catalyst powder.
[0153] The corn stalks were crushed by a crusher and passed through a 100-mesh sieve to obtain corn stalk powder with a particle size of less than 0.2 mm. 1 g of NiO / CaO·B2O3 composite catalyst powder and 10 g of the above corn stalk powder were added to 100 g of water, stirred evenly and transferred into a high-pressure reactor. The reactor was purged with nitrogen and sealed after detecting that there was no oxygen in the outlet air. The hydrothermal reaction was carried out at a temperature of 280 ° C and a holding time of 2 h. After the reaction was completed, the reactor was allowed to cool naturally to room temperature. The reaction product was poured out and filtered to obtain a first-level hydrothermal wood vinegar. After the third-level wood vinegar was stored at low temperature in the dark for 15 days, the crude wood vinegar was divided into 3 layers, the upper layer was a thin light oil phase layer, the middle was a liquid phase layer, and the lower part was a sedimentation tar layer. The middle liquid phase layer was taken out to obtain a refined hydrothermal wood vinegar.
[0154] Comparative Example 5 (composite catalyst + secondary hydrothermal)
[0155] Take 10g Ni(NO3)2·6H2O powder to prepare a solution with a mass concentration of 10%, take 1g CaO·B2O3·2H2O powder and disperse it into the prepared Ni(NO3)2·6H2O solution, stir for 20min and then ultrasonically disperse for 20min to completely disperse the CaO·B2O3·2H2O, let it stand for 3h, vacuum dry at 80℃ for 10h, calcine at 350℃ for 3h, grind, rinse with water, filter, and dry to obtain NiO / CaO·B2O3 composite catalyst powder.
[0156] The corn stalks were crushed by a crusher and passed through a 100 mesh sieve to obtain corn stalk powder with a particle size of less than 0.2 mm. 1 g of NiO / CaO·B2O3 composite catalyst powder and 10 g of the above corn stalk powder were added to 100 g of water, stirred evenly and transferred into a high-pressure reactor. The reactor was purged with nitrogen and sealed after detecting that there was no oxygen in the outlet air. The hydrothermal reaction was carried out at a temperature of 280°C and a holding time of 2 hours. After the reaction was completed, the reactor was naturally cooled to room temperature. The reaction product was poured out and filtered to obtain a first-grade hydrothermal wood vinegar.
[0157] Add water to the first hydrothermal wood vinegar obtained above to 100g, then add 1g NiO / CaO·B2O3 composite catalyst powder and 10g corn stalk powder, repeat the above hydrothermal and filtration steps to obtain a second hydrothermal wood vinegar. Then, after the second hydrothermal wood vinegar is stored at low temperature and away from light for 15 days, the crude wood vinegar is divided into 3 layers, the upper layer is a thin light oil phase layer, the middle is a liquid phase layer, and the lower part is a sedimentation tar layer. Take out the middle liquid phase layer to obtain a refined hydrothermal wood vinegar.
[0158] Comparative Example 6 (using only calcium borate + three-stage hydrothermal)
[0159] The corn stalks were crushed by a crusher and passed through a 100-mesh sieve to obtain corn stalk powder with a particle size of less than 0.2 mm. 1 g of CaO·B2O3·2H2O powder and 10 g of the above corn stalk powder were added to 100 g of water, stirred evenly and transferred into a high-pressure reactor. The reactor was purged with nitrogen and sealed after detecting that there was no oxygen in the outlet air. The hydrothermal reaction was carried out at a temperature of 280°C and a holding time of 2 hours. After the reaction was completed, the reactor was allowed to cool naturally to room temperature. The reaction product was poured out and filtered to obtain a first-grade hydrothermal wood vinegar.
[0160] Add water to the first hydrothermal wood vinegar obtained above to 100g, then add 1gCaO·B2O3·2H2O powder and 10g corn stalk powder, repeat the above hydrothermal and filtration steps to obtain a second hydrothermal wood vinegar. Add water to the second hydrothermal wood vinegar obtained above to 100g, then add 1gCaO·B2O3·2H2O powder and 10g corn stalk powder, repeat the above hydrothermal and filtration steps to obtain a third hydrothermal wood vinegar. Then, after the third hydrothermal wood vinegar is stored at low temperature in the dark for 15 days, the crude wood vinegar is divided into 3 layers, the upper layer is a thin light oil phase layer, the middle is a liquid phase layer, and the lower part is a sedimentation tar layer. Take out the middle liquid phase layer to obtain a refined hydrothermal wood vinegar.
[0161] Comparative Example 7 (using only nickel oxide + three-stage hydrothermal)
[0162] The corn stalks were crushed by a crusher and passed through a 100-mesh sieve to obtain corn stalk powder with a particle size of less than 0.2 mm. 1 g of NiO powder and 10 g of the above corn stalk powder were added to 100 g of water, stirred evenly and transferred into a high-pressure reactor. The reactor was purged with nitrogen and sealed after detecting that there was no oxygen in the outlet air. The hydrothermal reaction was carried out at a temperature of 280 ° C and a heat preservation time of 2 h. After the reaction was completed, the reactor was naturally cooled to room temperature. The reaction product was poured out and filtered to obtain a first-grade hydrothermal wood vinegar.
[0163] In the first hydrothermal wood vinegar obtained above, water is added to 100g, and then 1gNiO powder and 10g corn stalk powder are added, and the above hydrothermal and filtering steps are repeated to obtain a second hydrothermal wood vinegar. In the second hydrothermal wood vinegar obtained above, water is added to 100g, and then 1gNiO powder and 10g corn stalk powder are added, and the above hydrothermal and filtering steps are repeated to obtain a third hydrothermal wood vinegar. Then the third-level wood vinegar is stored at low temperature in the dark for 15 days, and the crude wood vinegar is divided into 3 layers, the upper layer is a thin light oil phase layer, the middle is a liquid phase layer, and the lower part is a sedimentation tar layer. Take out the middle liquid phase layer to obtain a refined hydrothermal wood vinegar.
[0164] Comparative Example 8 (direct mixing of nickel oxide + calcium borate + three-stage hydrothermal)
[0165] The corn stalks were crushed by a crusher and passed through a 100-mesh sieve to obtain corn stalk powder with a particle size of less than 0.2 mm. 0.1 g NiO powder, 0.9 g CaO·B2O3·2H2O powder and 10 g of the above corn stalk powder were added to 100 g water, stirred evenly and transferred into a high-pressure reactor. The reactor was purged with nitrogen and sealed after detecting that there was no oxygen in the outlet air. The hydrothermal reaction was carried out at a temperature of 280 ° C and a heat preservation time of 2 h. After the reaction was completed, the reactor was naturally cooled to room temperature. The reaction product was poured out and filtered to obtain a first-grade hydrothermal wood vinegar.
[0166] Add water to the first hydrothermal wood vinegar obtained above to 100g, then add 0.1g NiO powder, 0.9g CaO·B2O3·2H2O powder and 10g corn stalk powder, repeat the above hydrothermal and filtration steps to obtain a second hydrothermal wood vinegar. Add water to the second hydrothermal wood vinegar obtained above to 100g, then add 0.1g NiO powder, 0.9g CaO·B2O3·2H2O powder and 10g corn stalk powder, repeat the above hydrothermal and filtration steps to obtain a third hydrothermal wood vinegar. Then, the third hydrothermal wood vinegar is stored at low temperature in the dark for 15 days, and the crude wood vinegar is divided into 3 layers, the upper layer is a thin light oil phase layer, the middle is a liquid phase layer, and the lower part is a sedimentation tar layer. Take out the middle liquid phase layer to obtain a refined hydrothermal wood vinegar.
[0167] Table 1 Performance of the refined wood vinegar obtained by multi-stage catalytic hydrothermal treatment and the refined wood vinegar obtained by comparative examples 1 to 8
[0168]
[0169]
[0170] Table 1 Description:
[0171] The yield of the wood vinegar prepared in Example 6 was 300 ml / 100 g biomass, the total carbon content was 5.027 g / L, the relative content of total phenol was 40.00%, and the bactericidal ability against Staphylococcus aureus was 10.355-Log 10 (CFU / ml).
[0172] The yield of all examples was higher than 280 ml / 100 g biomass, the total carbon content was higher than 4.933 g / L, the relative content of total phenol was higher than 35.00%, and the bactericidal capacity was higher than 10.000-Log 10 (CFU / ml).
[0173] In terms of output, the wood vinegar prepared in this embodiment is much higher than that prepared by the traditional pyrolysis method. In terms of total carbon content, total phenol content and bactericidal ability, the wood vinegar prepared in this embodiment is higher than that prepared by the traditional pyrolysis method. This is mainly due to the following two points: (1) the addition of the NiO / CaO·B2O3 composite catalyst promotes the pyrolysis of biomass, catalyzes more furfural to convert into phenols and acids, and increases the relative content of antibacterial components in the wood vinegar; (2) the multi-stage hydrothermal strategy is adopted to effectively increase the content of total organic components in the wood vinegar.
[0174] In Table 1, (1) Comparative Example 1 uses a primary hydrothermal method to prepare wood vinegar, the total organic carbon content of the wood vinegar is 1.240 g / L, the total organic matter content is too low, and the bactericidal capacity of the prepared wood vinegar is only 8.150-Log 10 (CFU / ml). (2) Comparative Example 2 used hydrothermal oxidation to prepare wood vinegar. Although the yield and bactericidal capacity of wood vinegar were slightly increased compared with Comparative Example 1, the bactericidal capacity was only 8.166-Log due to the low content of total organic matter. 10 (CFU / ml). (3) Comparative Example 3 directly used three-stage hydrothermal to prepare wood vinegar. Compared with Example 6, the organic matter content in the prepared wood vinegar was slightly lower, and the total phenol content was significantly reduced, resulting in its bactericidal capacity of only 9.015-Log 10 (CFU / ml). (4) Comparative Example 4 used a composite catalyst and primary hydrothermal treatment, and the total organic carbon content in the wood vinegar was only 2.511 g / L, which was much lower than that in Example 6, resulting in a bactericidal capacity of only 8.838-Log 10(CFU / ml). (5) Comparative Example 5 used a composite catalyst and secondary hydrothermal treatment, and the total organic carbon content in the wood vinegar was only 3.540 g / L, which was much lower than that in Example 6, resulting in a bactericidal capacity of only 9.237-Log 10 (CFU / ml). (6) Comparative Example 6 only uses calcium borate and three-stage hydrothermal treatment, lacks the catalytic effect of NiO, resulting in a decrease in the content of phenolic substances in the prepared wood vinegar, a weakened bactericidal ability, and the inability to separate the catalyst from the biomass. (7) Comparative Example 7 only uses NiO and three-stage hydrothermal treatment, lacks the catalytic effect of calcium borate, resulting in a simultaneous decrease in the total organic matter content and total phenol content in the wood vinegar, and a decrease in the antibacterial property of the wood vinegar. (8) Comparative Example 8 directly mixes calcium borate powder and NiO powder as catalysts and performs three-stage hydrothermal treatment. Compared with Example 6, the antibacterial property of the prepared wood vinegar is not significantly reduced, but the catalyst cannot be recycled.
[0175] Figure 1 The picture of the wood vinegar prepared in Example 6 of the present invention killing Staphylococcus aureus and Escherichia coli, as can be seen from the figure, after contact with wood vinegar, the number of live colonies of Staphylococcus aureus and Escherichia coli on the agar plate is greatly reduced. It can be seen from the scanning electron microscope picture that after contact with wood vinegar, Staphylococcus aureus and Escherichia coli both showed dissolution, collapse and rupture of cell membrane and cell wall, and the cell structure was irreversibly damaged and died.
[0176] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A method for preparing wood vinegar by multi-stage catalytic hydrothermal method, characterized in that: The following steps are involved: (1) dispersing calcium borate in a nickel nitrate hexahydrate solution at a molar ratio of calcium to nickel of 1 to 4:11, allowing to stand after being evenly dispersed, drying, and calcining to obtain a nickel oxide / calcium borate composite catalyst; (2) using water as the reaction medium, hydrothermally reacting the biomass with the nickel oxide / calcium borate composite catalyst at 200-350° C. for 0.5-2 h, filtering to obtain a first-grade hydrothermal wood vinegar solution, and recovering the nickel oxide / calcium borate composite catalyst; (3) adding the biomass and the nickel oxide / calcium borate composite catalyst to the primary hydrothermal wood vinegar solution, performing a hydrothermal reaction at 200-350° C. for 0.5-2 h, filtering to obtain a secondary hydrothermal wood vinegar solution, and recovering the nickel oxide / calcium borate composite catalyst; (4) Referring to step (3), the biomass and the nickel oxide / calcium borate composite catalyst are added to the N-grade hydrothermal wood vinegar solution, and the solution is hydrothermally reacted at 200-350° C. for 0.5-2 h, filtered to obtain the N+1-grade hydrothermal wood vinegar solution, and the nickel oxide / calcium borate composite catalyst is recovered at the same time; N is an integer and ≥ 2, that is, the operation of repeatedly adding biomass and nickel oxide / calcium borate composite catalyst to the latest hydrothermal wood vinegar to carry out hydrothermal reaction is performed to obtain multi-stage catalytic hydrothermal crude wood vinegar, and after layering, the middle aqueous phase is taken to obtain refined hydrothermal wood vinegar.
2. A method for preparing wood vinegar by multi-stage catalytic hydrothermal method according to claim 1, characterized in that: The weight ratio of the biomass to the nickel oxide / calcium borate composite catalyst in steps (2) to (4) is 10:1 to 3; the weight ratio of the biomass to water in step (2) is 1:10 to 20; and in the reaction system of steps (3) to (4), the weight ratio of the biomass to the liquid is 1:10 to 20.
3. A method for preparing wood vinegar by multi-stage catalytic hydrothermal method according to claim 1, characterized in that: The calcium borate in step (1) is CaO•B2O3•2H2O; the weight ratio of CaO•B2O3•2H2O to Ni(NO3)2•6H2O is 0.5-2:10; The mass concentration of the nickel nitrate hexahydrate solution in step (1) is 5-15%.
4. The method for preparing wood vinegar by multi-stage catalytic hydrothermal method according to claim 1, characterized in that: The standing time in step (1) is 1 to 5 hours; the calcination temperature in step (1) is 300 to 400°C and the time is 2 to 4 hours; the calcination is carried out in a nitrogen and / or inert gas atmosphere, wherein the inert gas refers to a rare gas.
5. The method for preparing wood vinegar by multi-stage catalytic hydrothermal method according to claim 1, characterized in that: In step (4), N satisfies 2≤N≤5; the temperature of the hydrothermal reaction in steps (2) to (4) is 230-270°C and the time is 1-2h; or the temperature is 270-300°C and the time is 0.5-1h.
6. The method for preparing wood vinegar by multi-stage catalytic hydrothermal method according to claim 1, characterized in that: The biomass in steps (2) to (4) is biomass powder; the biomass in steps (2) to (4) is agricultural and forestry waste, specifically at least one of corn stalks, sugarcane bagasse, corn cobs, cotton stalks and wood fibers, and the wood fibers are at least one of poplar, bamboo and masson pine.
7. The method for preparing wood vinegar by multi-stage catalytic hydrothermal method according to claim 1, characterized in that: The amount of biomass used in steps (2) to (4) is the same, and the amount of nickel oxide / calcium borate composite catalyst used is the same; the hydrothermal reaction in steps (2) to (4) is carried out in a high-pressure reactor.
Citation Information
Patent Citations
Method for preparing high-content and high-added value chemical pyroligneous liquor under hydrothermal condition
CN106554792A